IMPLEMENTASI AKAD KERJASAMA SYARIAH ANTARA BPJS KESEHATAN DAN RS RIDHOKA SALMA CIKARANG - Sultan Antus Nasruddin; Salsabila Al-Hasni (JURNAL ILMIAH NUSANTARA, 2026)
The DSN-MUI Fatwa No. 107/2016 requires Islamic hospitals to establish cooperation with Islamic financial institutions. However, in practice, collaborations between Islamic hospitals and BPJS Kesehatan (Indonesia’s national health insurance agency) are still common, raising concerns regarding the compliance of such agreements with Sharia principles and the reliance of Islamic hospitals on conventional institutions. This study aims to analyze the contractual mechanism applied in the cooperation between Ridhoka Salma Islamic Hospital and BPJS Kesehatan and to evaluate its conformity with DSN-MUI Fatwa No. 107/2016 and Fatwa No. 98/2015. A qualitative case study approach was employed, collecting primary data through interviews with the Sharia Committee and hospital management, as well as direct observation of BPJS patient services, and secondary data from fatwas, regulations, agreements, books, and scholarly articles. The findings reveal that the cooperation is conducted through an Ijarah ‘ala al-A‘mal contract, which restricts the scope of transactions to services directly managed by the hospital. Sharia compliance is maintained through the mechanism of takhsis, grounded in the principles of ḥājjah ‘āmmah, maṣlaḥah mursalah, and ḥifẓ al-nafs, supported by active supervision of the Sharia Supervisory Board and mitigation of potential non halal revenues. Therefore, the cooperation can be considered compliant with Sharia principles as stipulated in the DSN-MUI fatwas.